Citation Analysis of Doctoral Theses on Botany Completed at the University of Burdwan (2000-2019) (LIS TODAY, 2023)
The purpose of this study is to examine the distribution of botany theses at The  University of Burdwan from 2000 to 2019 and to oversee research, analyse the performance  in a particular field, determine the mean number of written citations for botany, and assess  research collaboration using citation authorship. Taking this investigation's findings into  consideration, data were collected, analysed, and produced. The scientific research has  changed over time, citation analysis of 79 PhD theses of botany completed at The University  of Burdwan from 2000 to 2019 has been done. There are 23527 bibliographic references in  the 79 botany PhD theses. The mean number of references each thesis is 297.81.The study  found that the trend in authorship was toward team works instead of works done by one  person. Even though the number of single-author contributions has been going down, they  are still being made. There was also an analysis of how different aspects of the cited  literature changed over time. The rate of collaboration, as well as the supervisory pattern,  authorship pattern, and productivity of theses according to year, are all subjected to  research. In order to determine what kinds of documents are most often used in the research  activity, the citations are examined. This descriptive study examines the progression of the  research activities that followed University of Burdwan Botany Doctorate degrees.
Keywords: Citation Analysis; Botany; Supervisors; Authorship; References